P–528 rDNA methylation of human oocytes of women undergoing intracytoplasmic sperm injection (ICSI) increases with maternal age. (6th August 2021) - Trapphoff, T; Dieterle, S; Potabattula, R; Haaf, T
Abstract: Study question: Is there a correlation between the age of women undergoing ICSI and methylation pattern of rDNA core promoter and upstream control element in immature human oocytes? Summary answer: Methylation levels of the upstream control element and the rDNA core promoter in immature human oocytes increase with age of women undergoing ICSI. What is known already: Methylation of ribosomal DNA (rDNA) in germ cells regulates temporary and spatially highly coordinated nucleolar activity, cellular metabolism, and thus developmental potential of the early embryo. Alterations of methylation pattern may therefore cause dysregulation of genes and signal cascades resulting in limited fertility. It has been shown that the methylation of sperm rDNA increases with the donor's age. The positive correlation between sperm rDNA methylation and age has been conserved among mammals during evolution including humans and mice. In contrast to sperm, little is known about the methylome of human oocytes and its role in human reproduction. Study design, size, duration: Consecutive women undergoing ICSI because of male subfertility were included. Patients with endometriosis, polycystic ovary syndrome, ovarian, uterine or breast cancer, as well as patients with an anti-Mullerian hormone level <1ng/ml were excluded. Immature oocytes (germinal vesicle; GV) collected during oocyte pick-up at the Fertility Centre Dortmund between 2018 and 2020 were examined. Participants/materials, setting, methods: Cumulus-free GV oocytes which were not usable for ICSI were rinsed in phosphate buffer and stored at –20 °C until further investigation. Multiplex-PCR followed by singleplex-PCRs were carried out on the rDNA core promoter and upstream control element. Methylation levels were quantified by bisulphite pyrosequencing. Two oppositely imprinted genes (hPEG3 and hGTL2) were used as controls to ensure correct amplification and bisulphite conversion. Spearman's-rank-order-correlation and Mann-Whitney-U-Test were used for statistical analysis. Main results and the role of chance: For each GV oocyte, nine different Cytosine-phosphate-Guanine dinucleotides (CpGs) were quantified by bisulphite pyrosequencing for the rDNA core promoter and 26 different CpGs for the upstream control element (UCE). 120 human single oocytes from 60 women were analyzed. Connected statistical analysis was used if one patient had more than one oocyte. The age of the included women ranged from 26 to 40 years (mean±SD 33.5±3.2). Only oocytes which showed a correct methylation pattern for at least one imprinting control gene (hPEG3 and hGTL2) were considered for analysis. Mean methylation level ranged from 2–31% (mean±SD 8.7±5.5) of the analyzed CpGs for the rDNA core promoter and from 3–36% (mean±SD 11.4±7.1) CpGs for UCE. Spearman's correlation analysis revealed that the methylation levels of the human oocyte rDNA core promoter and rDNA UCE significantly increased with the age of the donor (p < 0.05). Correlation coefficient for rDNA core promoter was r = 0.22 and for upstream control element r = 0.21. It is also interesting to note that different oocytes from the same donors can display enormous methylation variation. Regarding clinical parameters, no correlation was observed between the methylation pattern of the rDNA core promoter or UCE and the body mass index or smoking status, respectively. Limitations, reasons for caution: Limitations of this study include difficulties in extrapolating the findings to the general population, because no data of women not undergoing ICSI are available. Only GV-oocytes were analyzed. Additional research is needed to clarify the effect of different methylation pattern with increasing female age and its role in human reproduction. Wider implications of the findings: We propose that the increase of rDNA methylation in male and female germ cells with advanced age directly or indirectly influences the regulation of nucleolar activity, cellular metabolism, and thus the developmental potential of the early embryo. This age-dependent epigenetic effect may result in decreased human fertility. Trial registration number: NCT03565107